2021
DOI: 10.3389/fpsyg.2021.746975
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tai Chi and Qigong Exercise on Psychological Status in Adolescents: A Systematic Review and Meta-Analysis

Abstract: Background: The purpose of this study was to systematically review the effectiveness of Tai Chi and Qigong exercise on adolescents' symptoms of depression and anxiety, and psychological status based on clinical evidences, and to calculate the pooled results using meta-analysis.Methods: A systematic search using seven English and three Chinese databases was initiated to identify randomized controlled trials (RCT) and non-randomized comparison studies (NRS) assessing the effect of Tai Chi and Qigong exercise on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
4
16
0
1
Order By: Relevance
“…Depression and anxiety have been widely studied in previous epidemiological studies looking at the relationship between exercise and mental health [ 53 54 ]. The results of this review are consistent with the conclusions of a previously published review suggesting that Tai Chi and Qigong exercises contribute to reducing anxiety and depression symptoms [ 26 , 55 56 ]. Specifically, effect size estimates with respect to the effects of Qigong ranged from − 0.52 to − 1.94 for depression levels and from − 0.39 to − 0.78 for anxiety levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Depression and anxiety have been widely studied in previous epidemiological studies looking at the relationship between exercise and mental health [ 53 54 ]. The results of this review are consistent with the conclusions of a previously published review suggesting that Tai Chi and Qigong exercises contribute to reducing anxiety and depression symptoms [ 26 , 55 56 ]. Specifically, effect size estimates with respect to the effects of Qigong ranged from − 0.52 to − 1.94 for depression levels and from − 0.39 to − 0.78 for anxiety levels.…”
Section: Discussionsupporting
confidence: 90%
“…Although a narrative review analysed Tai Chi and Qigong for the treatment and prevention of mental disorders, it lacked a quantitative analysis [27]. A meta-analysis assessed the effect of Qigong exercise on psychological status in adolescents, but it was not based on RCTs and did not contain an analysis of physical functions [28]. Meanwhile, there are some studies containing meta-analyses of RCTs that have evaluated the effects of Qigong on physical [29][30] and mental health [31][32][33][34], but they focused mainly on middle-aged and elderly people with various diseases, with only a small part of them being young people.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, et al [25] examined the results of four random controlled trials and six non-randomized comparison studies involving a total of 1,244 adolescents to determine the effect of tai chi qigong exercises on the psychological status of adolescents. They found that tai chi and qigong exercises can reduce anxiety and depression as well as cortisol level.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…In the West, it is sometimes used in conjunction with mainstream medicine as a supplementary tool to treat symptoms of various diseases and ailments [1][2][3][4][5][6][7][8][9][10]. Numerous studies have found that qigong can aid in the treatment of arthritis [11], back pain [12], cancer [13][14][15][16][17], cognitive impairment [18,19], Covid-19 [20,21], COPD [22], depression and anxiety [23][24][25][26], fatigue [27], hypertension [28,29], muscle strength and posture [30], Parkinson's disease [31,32], stroke [33], and tertiary-care pain management [34].…”
Section: Introductionmentioning
confidence: 99%
“…Although a narrative review analysed Tai Chi and Qigong for the treatment and prevention of mental disorders, it lacked a quantitative analysis [28] . A meta-analysis assessed the effect of Qigong exercise on psychological status in adolescents, but it was not based on RCTs and did not contain an analysis of physical functions [29] . Meanwhile, there are some studies containing meta-analyses of RCTs that have evaluated the effects of Qigong on physical [30][31] and mental health [32][33][34][35][36] , but they focused mainly on middle-aged and elderly people with various diseases, with only a small part of them being young people.…”
Section: Introductionmentioning
confidence: 99%